Oral celecoxib versus oral diclofenac for post-perineal repair analgesia after spontaneous vaginal birth: a randomised trial - Lim, Soo Soo; Tan, Peng Chiong; Sockalingam, Jayanthi Karen; Omar, Siti Zawiah (Wiley, 2008)
Objective: To compare oral celecoxib with oral diclofenac as pain reliever after perineal repair following normal vaginal birth. Methods: One hundred and sixty-four and 165 women, respectively, were randomised to 200 mg celecoxib or to 100 mg diclofenac orally 12 hourly for 24 h after perineal repair. A ten-point visual analog scale (VAS) for pain recorded at one, two, four, eight, 12 and 24 hours at rest and when mobilising was the primary outcome. Results: Repeated measures analysis of variance showed a larger reduction of VAS pain score at rest with celecoxib compared to diclofenac (P = 0.044). Mean VAS pain score at rest was 2.2 versus 2.7, 2.1 versus 2.5, 1.8 versus 2.2, 1.6 versus 1.6, 1.3 versus 1.4 at one, two, four, eight, 12 and 24 hours, respectively, for celecoxib versus diclofenac. The difference in pain score when mobilising was not significant (P = 0.75). Univariate analyses with the Student's t-test indicated significantly lower pain score at rest only at one, two and four hours with celecoxib. Randomisation to celecoxib was associated with less upper gastrointestinal symptoms reported: 38 of 163 (23.3) versus 57 of 165 (34.5) (relative risk 0.67 95 CI 0.48â0.96: P = 0.029) but additional analgesia for breakthrough pain was not significantly different eight of 161 (5.0) versus 18 of 165 (10.9) (relative risk 0.46 95 CI 0.20â1.01: P = 0.065). Conclusion: Celecoxib was associated with a slightly lower VAS pain score at rest and less upper gastrointestinal symptoms were reported when compared to diclofenac.